Religious education as a factor of personality formation - O. Shnurova (Українське Pелігієзнавство, 2005)
Modern ethico-philosophical literature treats spirituality as a value characteristic of moral consciousness, although spirituality is a complex and multifaceted phenomenon. Therefore, this one-sided approach is wrong. In considering this problem, two approaches were identified: theological and purely philosophical (secular).